2020
DOI: 10.18510/hssr.2020.813
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Social Capital and Poverty Farmers in Aceh

Abstract: Purpose of the study: This study tried to examine the correlation between social capital and the poverty level of farmers in Aceh. It was linked to the uneven agricultural development of some rural areas in Aceh had caused the poverty rates in villages are higher than in the urban areas. Hence the social capital is important as other capitals in development and become the energies for the development and decreases the rate of poverty. Methodology: This research used a quantitative method by distributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Harrison et al (2019), who explored the relationship between social capital and poverty in the western part of the United States, found that communities with higher levels of social capital tended to have lower poverty rates and that poverty could impede the formation of social capital. Yunus et al (2020) examined social capital and the poverty rate among the poor in Indonesia. They found a significant positive correlation between social capital and poverty levels; people with greater social capital stocks had lower poverty rates.…”
Section: Clan-based Network and Povertymentioning
confidence: 99%
“…Harrison et al (2019), who explored the relationship between social capital and poverty in the western part of the United States, found that communities with higher levels of social capital tended to have lower poverty rates and that poverty could impede the formation of social capital. Yunus et al (2020) examined social capital and the poverty rate among the poor in Indonesia. They found a significant positive correlation between social capital and poverty levels; people with greater social capital stocks had lower poverty rates.…”
Section: Clan-based Network and Povertymentioning
confidence: 99%
“…However, accessible resources depend more on members' power position, network location, and social hierarchy (Bourdieu, 1986), while non-members could be excluded from social networks to show loyalty to the community. To gain membership, close contact or bonding connections are critical (Woolcock and Narayan, 2000;Yunus et al, 2020). More often, the in uential group takes advantage of its strong social network to gain resources for group members to promote private or sectarian interests (MacGillivray, 2018).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…First, we focus on Chinese domestic migrant workers (hereinafter referred to as migrant workers) who were severely affected by the COVID-19 pandemic and were neglected. Previous studies have documented that social capital can alleviate rural residents' poverty (Kamarni et al, 2019;Hong and Tisdell, 2017;Yunus et al, 2020), but there is little knowledge concerning migrant workers' social capital and poverty state.…”
Section: Introductionmentioning
confidence: 99%
“…Social capital in the management of SMEs is not an individual but collective endeavor as it involves the formation of a network of relationships, strengthening emotional bonds among individuals and groups and exchanging and rendering mutual support. Several studies show that strengthening social capital during Covid-19 pandemic contributes to making improvement in SME performance (Hao, Xiao, & Chon, 2020;Pitas & Ehmer, 2020;Shafi, Liu, & Ren, 2020;Yunus, Zainal, Jalil, & Sari, 2020); fosters the growth of new business networks, clus-ters, that are underpinned by social capital principles, and norms and values. The formation of business network clusters in turn enhances trust and competitiveness of SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Social capital has been associated with economic performance of enterprises. (Joe Wallis and Paul Killerby, 2004;Lockhart, 2005;Nixon Kamukama, 2013;Yunus et al, 2020). The advent of the Covid-19 pandemic disaster, elicits the need for society to adapt behavior to changing social and economic conditions.…”
Section: Introductionmentioning
confidence: 99%